INTEGRATION OF EMOTIONAL INTELLIGENCE TRAINING IN PARENTAL COUNSELING TO IMPROVE CHILD DEVELOPMENT: A QUALITATIVE STUDY - Rachma Arummawati; Silva Al Mahda (Islamic Counseling and Parenting Journal, 2024)
Intelligence emotional play a role important in development psychosocial children , especially through the role of parents in managing emotions . However , training intelligence emotional Not yet Lots integrated into the parent counseling program . This study aims to explore impact integration training intelligence emotional in parent counseling​ to development children . This study uses approach qualitative with method studies case , where data is collected through interview in-depth , observation participatory , and discussion group focused (FGD) on 15 parents who have follow training intelligence emotional for at least three months . The results of the study showed that parents who follow​ training intelligence emotional show improvement significant in awareness and management emotions , which have an impact positive on quality interaction with children . Children of parents involved in this training also showed development more emotional and social​ good . This study underlines importance integration training intelligence emotional in parent counseling programs to create environment more family​ supportive for development child